Double drainage consolidation of annular soil pile considering radial deformation - Han, Chao; Fan, Zhou; Liu, Sijie; Bai, Xinyue; Yu, Peng; Wu, Wei; Mao, Xintong; Liu, Yunfei; Liu, Zhiwei; Bai, Bin (Frontiers in Built Environment, 2025)
The resource utilization of silt with high water content is a major problem in the process of ecological dredging and engineering construction in recent years. It is a feasible way to realize the resource utilization of silt into hollow pile section by means of central pressure. The preparation of central pressurized annular soil pile is mainly based on the principle of soil drainage and consolidation, but the deformation direction and external force loading mode are different from the classical consolidation theory. Based on the connotation of this technique, the calculation model considering radial deformation is derived. Combining the control equation and solution conditions, the finite element solution of soil pile with the radial deformation is obtained. Based on this solution, the influence of the related factors in the preparation process of annular soil pile, including the initial water content, external load size, internal and external diameter size and nonlinear compression index, on the development of consolidation degree and the growth of internal diameter in the preparation process is studied.